2015
DOI: 10.1097/wnr.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low-frequency electromagnetic fields enhance the proliferation and differentiation of neural progenitor cells cultured from ischemic brains

Abstract: In the mammalian brain, neurogenesis persists throughout the embryonic period and adulthood in the subventricular zone of the lateral ventricle and the granular zone (dentate gyrus) of the hippocampus. Newborn neural progenitor cells (NPCs) in the two regions play a critical role in structural and functional plasticity and neural regeneration after brain injury. Previous studies have reported that extremely low-frequency electromagnetic fields (ELF-EMF) could promote osteogenesis, angiogenesis, and cardiac ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In our study we suggested that ELF-EMF improved neuroplasticity, which idea is compatible with data from the existing literature ( Oda and Koike, 2004 ; Cuccurazzu et al, 2010 ; Balassa et al, 2013 ; Cheng et al, 2015 ). Cuccurazzu et al (2010) investigated the effect of ELF-EMF (50Hz, 1mT) on hippocampal neurogenesis in adult mice.…”
Section: Discussionsupporting
confidence: 92%
“…In our study we suggested that ELF-EMF improved neuroplasticity, which idea is compatible with data from the existing literature ( Oda and Koike, 2004 ; Cuccurazzu et al, 2010 ; Balassa et al, 2013 ; Cheng et al, 2015 ). Cuccurazzu et al (2010) investigated the effect of ELF-EMF (50Hz, 1mT) on hippocampal neurogenesis in adult mice.…”
Section: Discussionsupporting
confidence: 92%
“…This “programming” of genomes in differentiating cells is instructed by environmental cues and, hence, is also likely to be sensitive to disturbance by environmental factors2223, such as EMFs. Consistent with a possible impact of ELF-MF exposure on epigenetic cell programming, it has been reported that ELF-MFs are able to alter neural differentiation24252627. Regulatory epigenetic modifications include the acetylation and methylation of histone tails and the methylation of DNA cytosine bases2829, altogether establishing three main classes of chromatin; i.e.…”
mentioning
confidence: 73%
“…However, the most important part of poststroke therapy is immediate and long-term rehabilitation, considering the enormous plasticity of the brain [ 3 ]. Although extremely low-frequency electromagnetic field (ELF-EMF) therapy is not a standard treatment in the poststroke rehabilitation, some authors suggest its increased positive effect on patients [ 4 ]. ELF-EMF treatment is based on regeneration, osteogenesis, analgesics, and anti-inflammatory action.…”
Section: Introductionmentioning
confidence: 99%